Relief carvings of geometric floriated patterns around the adhisthana - Temples of India Project Team (Jio Institute, 2024)
Broken fragments and debris from the original temple assembled on the adhisthana on the southeast side. Relief carvings of geometric floriated patterns can be seen all around the adhisthana.